Treatment of 23 Cases of Supraorbital Neuralgia by Acupuncture plus Semi-conductive Laser - 涂小华 杨罗艳 李增利 (Journal of acupuncture and tuina science, 2007)
Summary23 cases of the patients with supraorbital neuralgia were treated by puncturing Yangbai (GB 14) toward Yuyao (Extra), Zanzhu (BL 2), Taiyang (Extra), Touwei (ST 8), Zhongzhu (TE 3) and Neiting (ST 44) on the sick side, plus laser radiation on a site about 1 cm apart from the midpoint of the eyebrow of the sick side. After 10 treatments, the results showed cure in 19 cases and remarkable effect in 4 cases.